Woolf, History, Us - Melba Cuddy-Keane (Interdisciplinary/Multidisciplinary Woolf, 2013)
History was the focus of my very first presentation at a Woolf conference, at Bard College in 1994. The motivation for that paper was a chance remark by a very UnWoolfian administrator at my own university: “£500 a year? What would that mean now? $100,000? $500,000? Woolf was so out of touch with real life.” My response was captured in my title “Opening Historical Doors to theRoom.” To understand Woolf’s metaphor, and the material foundation that supported it, I argued, we needed to engage both monetary and psychological conversion: in addition to knowing what £500 would mean in 1990s